PERGESERAN NILAI PILAR DEMOKRASI DALAM KERANGKA OTONOMI DAERAH - Kholik, Saeful (Universitas Wiralodra, 2020)
In a government organization, the expertise of the law making is most accumulated. It enables the law making process to be easily done by law the enforcers. This fact causes the role of government to be central. It also lead to an access of government organizations to become very powerful over the functions of organizations that exist within and outside the government. Therefore, to avoid concentration of power in the hands of government organizations, the idea arises to hold a separation and division of powers. The emergence of a constitutional idea of ​​a rule of law basically changes the power of the government. It makes their existence is not too dominant to see the Indonesian government system recognizing regional government and regional autonomy which are basically capable of impacting in the system of pillars of the democratic legal order. The shift of legislative and executive power within the framework of regional autonomy has indeed occurred with the dynamics of a structurally structured and infrastructural political life. It has an authority over each of the institution's committees. It acts an important function and even considered as the main function of the parliamentary institution. Important function is the legislative institution that is the institution legislators or institutions that determine the making of the law.